2022
DOI: 10.1039/d2qo01383e
|View full text |Cite
|
Sign up to set email alerts
|

Advances in circularly polarized electroluminescence based on chiral TADF-active materials

Abstract: Due to the promising application prospect of circularly polarized organic light-emitting diodes (CP-OLEDs) in the future display and optoelectronic technology, especially in the display screen, recently, a variety of chiral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 67 publications
0
19
0
1
Order By: Relevance
“…2023, 11,2202787 candidates for constructing high-efficiency CP-OLEDs, which is attributed to the fact that TADF compounds possess high radiative decay rates and fluorescence efficiency by efficiently harvesting triplet states through reverse ISC process from T1 to S1 states. [254][255][256][257] Hu et al reported TADF-active poly(carbazoleran-acridine)s with CPL property by introducing chiral alanine pendant into the polymer side chains. [258] The corresponding OLEDs displayed a maximum brightness and maximum current efficiency of 1477 cd m −2 and 2.52 cd A −1 , respectively.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
See 1 more Smart Citation
“…2023, 11,2202787 candidates for constructing high-efficiency CP-OLEDs, which is attributed to the fact that TADF compounds possess high radiative decay rates and fluorescence efficiency by efficiently harvesting triplet states through reverse ISC process from T1 to S1 states. [254][255][256][257] Hu et al reported TADF-active poly(carbazoleran-acridine)s with CPL property by introducing chiral alanine pendant into the polymer side chains. [258] The corresponding OLEDs displayed a maximum brightness and maximum current efficiency of 1477 cd m −2 and 2.52 cd A −1 , respectively.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Recently, CPL materials with thermally activated delayed fluorescence (TADF) properties have emerged as promising candidates for constructing high‐efficiency CP‐OLEDs, which is attributed to the fact that TADF compounds possess high radiative decay rates and fluorescence efficiency by efficiently harvesting triplet states through reverse ISC process from T1 to S1 states. [ 254–257 ] Hu et al. reported TADF‐active poly(carbazole‐ran‐acridine)s with CPL property by introducing chiral alanine pendant into the polymer side chains.…”
Section: Newly Emerging Categories Of Polymer‐based Circularly Polari...mentioning
confidence: 99%
“…It can oscillate from AE2 for pure circular emissions to 0 for unpolarized emissions, thus providing a quantitative estimation of circularly polarized emitted radiation over the total emitted radiation. Despite the numerous potential applications of this property [8][9][10][11][12][13][14][15] we want to focus on information encoding in the solid state. Within this context, the identification of the CPL sign from a luminescent material in different parts of a solid surface could be the base of a chiral barcoding.…”
Section: Introductionmentioning
confidence: 99%
“…22 In this case, the tethering of a chiral moiety to an active (achiral) fluorophore can induce chiroptical properties on a potentially large number of emitters, as recently exemplified in the development of CPL-SOMs exhibiting thermally activated delayed fluorescence properties. 23,24 Whereas intrinsically chiral fluorophore can reach important g lum values (up to 0.15 to the best of our knowledge 25 ), they often require cumbersome synthesis as well as the need of additional chiral purification steps in order to obtain enantiomerically pure samples. On the other hand, whereas chiral excitonic coupling or chiral perturbation-based emitters allow much easier access to a wide variety of CPL-active fluorophores, gaining a better comprehension of the structural parameters regulating their dissymmetry factors is still needed in order to unlock their true potential in terms of applications.…”
Section: Introductionmentioning
confidence: 99%